2015
DOI: 10.1002/jbm.a.35569
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of soy protein: A brief overview

Abstract: Soy protein (SP) based materials are gaining increasing interest for biomedical applications because of their tailorable biodegradability, abundance, being relatively inexpensive, exhibiting low immunogenicity, and for being structurally similar to components of the extracellular matrix (ECM) of tissues. Analysis of the available literature indicates that soy protein can be fabricated into different shapes, being relatively easy to be processed by solvent or melt based techniques. Furthermore soy protein can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 146 publications
(243 reference statements)
0
61
0
Order By: Relevance
“…[1] Alternatively, soy protein has also been explored more recently as a “green” and renewable substitute for petroleum- or animal-derived polymers in biomedical applications. [2] It was found that soy protein has bioactive peptides similar to extracellular matrix (ECM) proteins, present in human tissues. [3] These ECM-mimetic peptides can promote cell adhesion, proliferation, and migration critical for supporting tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Alternatively, soy protein has also been explored more recently as a “green” and renewable substitute for petroleum- or animal-derived polymers in biomedical applications. [2] It was found that soy protein has bioactive peptides similar to extracellular matrix (ECM) proteins, present in human tissues. [3] These ECM-mimetic peptides can promote cell adhesion, proliferation, and migration critical for supporting tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[3, 9b, 9c] Soy phytoestrogens have demonstrated to accelerate the healing process via ER-mediated signaling pathways. [8b, 8c, 10] They also possess anti-bacterial, [2b, 11] anti-inflammatory, [12] and anti-oxidant properties [13] that support and enhance wound healing. Moreover, clinical trials have reported that oral intake of soy (both protein and phytoestrogens) accelerates skin regeneration in aged women and burn patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the disadvantages of the previously used methods for microencapsulation, such as difficulties in scale-up and high costs of the emulsion method (14), and significant probiotic viability loss when spray drying method was combined with freeze drying (16), in this study, an attempt was made to achieve high viability of L. casei 01 during processing, storage and digestion by its encapsulation in alginate and soy protein isolate (SPI) microparticles using spray drying only. The SPI was chosen due to its confirmed nutritional and health benefits, availability, biodegradability, low immunogenicity and similarity with the components of the tissue extracellular matrix (20,21). It can be easily processed and linked to other biocompatible polymers, giving materials with enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Poly vinyl alcohol (PVA) is water soluble, nontoxic, good chemical and physical properties a non-toxic, film making ability and biodegradability nature (Chandy et al,1992 biocompatibility, blood compatibility and it also used as medical device (Sahoo et al,2009;Sahoo et al,2010;Tansaz et al 2016;Jegal et al,1999;Mallapragada et al,1996).…”
Section: Introductionmentioning
confidence: 99%